Peran Debt To Equity Ratio dalam Memediasi Pengaruh Current Ratio dan Institutional Ownership terhadap Dividend Payout Ratio pada Perusahaan Manufaktur - Ika Rosyada Fitriati; Nungki Pradita (Business Management Analysis Journal (BMAJ), 2019)
This study aims to examine the effect of current ratio variables and institutional ownership on dividend payout ratio and the role of debt to equity ratio in mediating those effects. The sampling method that is used in the study is purposive sampling method. This study uses financial statement data published in Indonesian Capital Market Directory (ICMD). The feasibility test of the model was tasted using a multicollinearity test, test the coefficient of determination and significance test. Path analysis and sobel test are used in hypothesis testing. The result of the study found that the current ratio has a significant negative effect on the debt to equity ratio, the debt to equity ratio has a significant negative effect on the dividend payout ratio and the debt to equity ratio is able to mediate the effect of the current ratio on the dividend payout ratio.